Evaluation of Apoptosis in Peripheral Human Lymphocytes Exposed to Rapamycin - Prochnow, Taísa Aozani; Carpio, Virna Nowotny; Dias, Esther Cristina Aquino; Manfro, Roberto Ceratti; Gonçalves, Luiz Felipe Santos (Brazilian Journal of Transplantation, 2005)
The influence of immunosuppressant drugs in regulating the activated lymphocytes and their role in controlling the immune response to human allografts is still yet to be determined. The aim of this study was to evaluate the induction of apoptosis by rapamycin in peripheral human lymphocyte. Methods: Mononuclear polymorphs were obtained from blood of healthy donors. Isolation was performed by Lymphoprep. Cells were cultured for 24 and 48h on 24 phytohemagglutinin-coated (PHA) well plates and/or rapamycin, as specified to the test. Four experimental culture tests were performed: non-stimulated lymphocytes, stimulated by PHA lymphocytes, non-stimulated lymphocytes, exposed to rapamycin and stimulated by PHA lymphocytes, and lymphocytes exposed to rapamycin. Apoptosis was determined by Annexin V-EGFP staining to externalized phosphatidyllserine on FACScan cytometer. Results: There was no statistically significant difference in the apoptosis detection in lymphocyte cultures with and without rapamycin both in 24h (7,1% + 3,8 x 6,6% + 2,6, p=1,0) and after 48h ( 6,1% + 1,9 x 6,2 + 1,8, p=1,0 ). However whenever the lymphocytes cultures were PHA-stimulated in the presence or absence of rapamycin, there was a statistically significant increase in the apoptosis in 24h and 48h. The addition of rapamycin to PHA stimulated cultures did not signicantly increase the percentage of lymphocyte apoptosis either after 24h (P=0.69), and after 48h (P=0.73). Conclusion: These data suggest that rapamycin does not induce apoptosis in a lymphocytes culture whether stimulated or not with PHA.